G613 SCIN: surveillance of congenital ichthyosis in neonates in UK and Ireland: a BPSU interim report. (25th October 2020) - Roked, F; Dewsbery, K; Khan, M; Ewer, A; Ibbs, S; Tyler, C; Moss, C
Abstract : Ichthyosis is a group of incurable genetic skin conditions. Severe types usually present at birth as collodion membrane (CM) or harlequin ichthyosis (HI): the latter has a neonatal mortality rate of up to 44%. 1 There is no proven correct treatment so the neonatal management of these babies varies. We aim to establish the incidence, neonatal management and mortality of CM and HI in UK and Ireland. Paediatricans and neonatologists report cases using the British Paediatric Surveillance Unit (BPSU) orange card scheme. https://www.rcpch.ac.uk/bpsu-study-.congenital-ichthyosis. The study commenced on 01/11/2018 and will run for 2 years. We collect data from reporting clinicians at 1 and 12 months. In the first 10 months we recorded 16 babies with CM (9 male, 7 female) and none with HI. Ten were white Caucasian, 4 were Irish, Indian or Caribbean and 2 were of mixed ethnicity, with no parental consanguinity. Four had a family history of ichthyosis. Median gestation was 37+1 (range 32+3 to 40+3). Median birthweight was 2.9 kg (range 2.24 to 3.67 kg). Both values are below the national average of 37 weeks and 3.25 kg respectively. 2 APGAR at 10 minutes was 9 or 10 in all patients. Two babies died: one on day 8 with presumed autosomal recessive ichthyosis and one with trichothiodystrophy on day 97. Those surviving were discharged at a median of 14 days (range 2–30). In terms of neonatal management, 3 babies were intubated and 8 had central venous access. All were treated with emollients, 9 with antibiotic and none with acitretin. All but 2 patients were handled by the parents at the time of the questionnaire being returned. All patients were seen by dermatologists, at a median of 1 day from birth, and by ophthalmologists at median 3 days from birth. Our data shows wide variation in neonatal management and significant mortality. This data will support an application to NHS England for funding for a highly specialised service for severe ichthyosis. We urge colleagues to notify us of all new casesto ensure an accurate national picture. References: Rajpopat S, Moss C, Mellerio J, et al. Harlequin ichthyosis: a review of clinical and molecular findings in 45 cases. Arch Dermatol . 2011 Jun;147(6):681–6 Birth characteristics in England and Wales: 2017. Office of National Statistics. https://www.ons.gov.uk/peoplepopulationandcommunity/birthsdeathsandmarriages/livebirths/datasets/birthcharacteristicsinenglandandwales